Role of Vitamin C in Skin Diseases - Wang, Kaiqin; Jiang, Hui; Li, Wenshuang; Qiang, Mingyue; Dong, Tianxiang; Li, Hongbin (Frontiers in Physiology, 2018)
Vitamin C (ascorbic acid) plays an important role in maintaining skin health and can promote the differentiation of keratinocytes and decrease melanin synthesis, leading to antioxidant protection against UV-induced photodamage. Normal skin needs high concentrations of vitamin C, which plays many roles in the skin, including the formation of the skin barrier and collagen in the dermis, the ability to counteract skin oxidation, and the modulation of cell signal pathways of cell growth and differentiation. However, vitamin C deficiency can cause or aggravate the occurrence and development of some skin diseases, such as atopic dermatitis (AD) and porphyria cutanea tarda (PCT). Levels of vitamin C in plasma are decreased in AD, and vitamin C deficiency may be one of the factors that contributes to the pathogenesis of PCT. On the other hand, high doses of vitamin C have significantly reduced cancer cell viability, as well as invasiveness, and induced apoptosis in human malignant melanoma. In this review, we will summarize the effects of vitamin C on four skin diseases (porphyria cutanea tarda, atopic dermatitis, malignant melanoma, and herpes zoster and postherpetic neuralgia) and highlight the potential of vitamin C as a therapeutic strategy to treat these diseases, emphasizing the clinical application of vitamin C as an adjuvant for drugs or physical therapy in other skin diseases.